Molecular phylogeny of the panpulmonate groups Stylommatophora and Hygrophila - Saadi, Ahmed (2020)
The phylogenetic relationships at the base of the stylommatophoran land snails and slugs have proven to be controversial, particularly the position of the Scolodontidae in relation to other stylommatophoran taxa. Likewise, the phylogenetic relationships within the hygrophilan freshwater snails and limpets are uncertain. This study provides molecular phylogenies for the Stylommatophora and Hygrophila at multiple scales including deep phylogenetic relationships of the major stylommatophoran and hygrophilan clades and family level relationships within the Orthurethra and Lymnaeoidea.